DAMPAK RESIDU LUMPUR SAWIT DAN DOLOMIT TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) DI ULTISOL - Arif Nugroho; Herry Gusmara; Bilman Wilman Simanihuruk (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[THE IMPACT OF PALM OIL SLUDGE RESIDUES AND DOLOMITE RESIDUES ON GROWTH AND YIELD OF PEANUT (Arachis hypogaea L.) IN ULTISOL].  This study aims to determine the best interaction between palm oil sludge (POS) residues and dolomite residues, determine the best POS residue, and determine the best dolomite residue in the growth and yield of peanut plants. This research was conducted from March 2018 to June 2018, the design used was a Complete Randomized Block Design (RCBD) with two factors. The first factor is POS residue with 3 levels, 0, 10, and 20 tons/ha. The second factor is dolomite residue with 4 levels, namely 0, 2, 4, and 6 tons/ha. The results showed that the best treatment combination was obtained from oil POS residue of 10 tons/ha and dolomite residue of 2 tons/ha which produced the highest total root nodule weights of 0.2417 g. POS residue of 20 tons/ha gives the highest yield on the growth component, which is an average plant height of 16.72 cm. POS residue of 10 tons/ha gave the highest yield on the growth component, namely dry stover weight of an average of 9.57 g, as well as the yield component of 45.20 total pods, 32.84 pods, total pod weight 43.47 g, and the weight of pith pods weighing 36.60 g. The highest total dry pod weight was 2.71 tons/ha. Dolomite residue gave a higher yield on all growth variables and observed results, with the highest total dry pod weight being 2.68 tons/ha.